The Effect of Final Rinse Agitation with Ultrasonic or Diode laser on Coronal Microleakage of Root-Canal Treated Teeth - Ramazani, Mohsen; Asnaashari, Mohammad; Ahmadi, Roghayyeh; Zarenejad, Nafiseh; Rafie, Alireza; Yazadani Charati, Jamshid (Iranian Endodontic Journal, 2019)
Introduction: This in vitro study aimed at comparing the effect of agitating the final irrigant solutions of root canal by ultrasonic or using 808 nm Diode laser on the apical seal of canal. Methods and Materials: A total of 90 extracted human maxillary central incisors were prepared up to size #45 and were randomly assigned to 4 experimental groups (n=20) and two control groups (n=5) respectively, as follows: I): 3 mL of 5.25% NaOCl was agitated as final irrigant solution with ultrasonic for 30 sec. The ultrasonic tip was 1 mm shorter than the working length, II): 3 mL of 5.25% NaOCl was agitated as final irrigant with 808 nm Diode laser for 30 sec. Fiber tip, placed in 1 mm shorter from working length was spirally moved coronally, III): 3 mL of 17% EDTA was agitated as final irrigant with 808 nm Diode laser for 30 sec and was applied similar to group II, IV): 3 mL of 17% EDTA was stimulated as final irrigant with ultrasonic for 30 sec and was applied similar to I. Apical seal was assessed by Dual Chamber technique using Bovine Serum Albumin protein. Kruskal-Wallis and Mann Whitney tests were used with significance level lower than 0.05% for statistical analysis. Results: The average leakage in the negative control, positive control, and groups I, II, III, IV were: 0.00, 13.5±5.1, 1.72±2.9, 5.12±5.6, 3.36±3.7, 2.4±4.2, respectively. Statistical analysis showed significant difference between groups (P<0.05). There was a significant difference between groups 1 and 2 in terms of protein leakage. Conclusion: Agitating 5.25% sodium hypochlorite solution as the final irrigant with ultrasonic is more effective in apical leakage reduction compared to other groups. Keywords: Apical Seal; Diode Laser; Irrigant Agitation; Irrigant Solution; Diode Laser; Ultrasonic